Effectiveness of (Active) Lifestyle Interventions in People With a Lower Limb Amputation: A Systematic Review - Sybel Van Helm, BSc; Leonie Adriana Krops, PhD; Rienk Dekker, MD, PhD; Aline Hendrike Vrieling, MD, PhD (Archives of Rehabilitation Research and Clinical Translation, 2022)
Objective: To explore the effectiveness of (active) lifestyle interventions for the health of people with a lower limb amputation in order to offer effective interventions during rehabilitation that may improve physical and psychosocial functioning of people with lower limb amputation. Data Sources: PubMed, CINAHL and Embase were searched from inception to February 2021. Study Selection: Inclusion criteria were (1) (quasi-)randomized controlled trial; (2) minimum of 10 participants with a lower limb amputation; (3) lifestyle intervention focusing on physical activity, smoking habits, alcohol use, nutrition, and/or stress management; (4) focus on health outcomes; (5) participants older than 18 years; (6) studies in Dutch, German, or English; and (7) primary research. Title, abstract, and full-text screening and quality assessment were performed by 2 independent assessors. Data Extraction: Of 2460 studies identified, 13 studies were included in this review. Two studies were of moderate methodological quality, 2 studies were of medium quality, and 9 studies were of poor quality. Data Synthesis: Lifestyle interventions in the included studies focused on physical activity and stress management. These interventions seemed effective for improving physical fitness, walking capacity, changes in body mass, quality of life, and intensity of physical activity. Conclusion: Lifestyle interventions focusing on physical activity and stress management seem effective for improving physical and psychosocial functioning of people with a lower limb amputation. However, the findings should be interpreted with caution given the limited methodological quality of the included studies. Future research should evaluate the effectiveness of interventions on nutrition, smoking habits, and alcohol use and the effectiveness of combined interventions in people with a lower limb amputation.